Groups of interlocution as a technique of productionand sistematization on Education research - Soares Ferreira, Liliana; Pereira Alves Fiorin, Bruna; de Castro do Amaral, Cláudia Letícia; Severo Maraschin, Mariglei (Revista Diálogo Educacional, 2014)
This article discusses research on education nowadays, based on a critical perspective of reality, considering the use of interlocution groups as a suitable technique to that. In educational field, researches becomes formal, a pedagogical action; whose aims reveal the institution and researcher’s intention. The interlocution group is presented as an interaction moment between the researcher and the researched individuals in order to socialize the results of the study and to discuss about those data and about issues that need clarification. Through language, each research individual presents his/her conceptions, influenced by his/her experiences, but since this moment of dialogue and interaction, they will be able to socialize and discuss the theme with individuals which possibly have something in common with the rest of the group due to their proximity with the developing research. It considers that groups of interlocution are more than data collection, presentation or quantification; it is a moment of problematization about the research.